GAJAH SUMATERA DALAM KARYA LUKIS REALIS KONTEMPORER - Heryan Pandu Pratama, Drs. Erfahmi, M.Sn., Drs. Ariusmedi, M.Sn. (Universitas Negeri Padang, 2018)
The creation of this final work aims to visualize Sumatran elephants in contemporary realist paintings. Showing the condition of Sumatran elephants that are increasingly threatened with extinction. The method and process of making works done in the creation of painting works through several steps: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of Concepts, (5) Settlement. The results of visualization of Sumatran elephants in contemporary realist paintings reveal the condition of Sumatran elephants that are threatened or die due to poaching or intentionally killed, in the form of 10 works with the title: (1) One by one, (2) My Ivory, (3) Boundary, (4) Suffering, (5) Concern, (6) Trying to survive, (7) Shackled, (8) Shackled # 2, (9) lamenting, (10) Alone.Kata kunci: gajah Sumatera, seni lukis, realis, realis kontemporer